Non-Nominative Subjects in Rajasthani and Central Pahari. The Status of the Ergative and Obligatory Constructions - Stroński, Krzysztof (Lingua Posnaniensis, 2010)
It was noted very early (Kellog 1972 [1875]; Grierson 2005 [1916], vol. IX , part IV : 103–107) that Rajastahani and Pahari dialects displayed many morphological affinities. However languages belonging to both groups show different treatment of non-nominative subjects in ergative and obligatory constructions. Western Rajasthani is an example of constant drift towards nominativity and disappearance of the oblique subject marking in the ergative domain (cf. Khokhlova 2001; 2006). Eastern Rajasthani reinforces the A and O contrast by introducing the ne postposition which serves as a dative marker as well. Pahari dialects on the other hand consistently mark A of the transitive sentence with the le postposition which is also employed as an instrumental marker. Those dative and instrumental markers are also used in the obligatory constructions. Both types of markers are of recent origin but the ergative and obligatory patterns can be observed throughout the history of the IA languages. In Rajasthani and Pahari one can see two divergent morphological developments which have resulted in attrition and reinforcement of ergativity respectively. The situation seems to be more complex if we take into consideration specific developments in verbal agreement in Rajasthani and the maintenance of unmarked pronominal O in Kumauni (cf. Sharma 1987) in ergative construction and the reinterpretation of the obligatory construction as future tense in Kumauni and Garhwali. The present paper argues that despite the recent origin of case marking in IA languages they do share certain structural properties which are traceable historically. Introduction of new markers has served only to maintain structural pattern continuum. The employment of the ergative postposition with intransitive verbs (e.g. cough, laugh) (cf. Montaut 2004) and its implementation in the obligatory construction can be perceived as an attempt to rebuild the system which goes back neither to the ergative nor to accusative (cf. Klimov 1983; Lehmann 1995; Bauer 2000).